STUDENTS’ WRITING IN PRE-TEST AND POST-TEST OF IE (INTEGRATED ENGLISH) 2015 PROGRAM IN STATE UNIVERSITY OF SURABAYA (UNESA) (RETAIN, 2017)
STUDENTS’ WRITING IN PRE-TEST AND POST-TEST OF IE (INTEGRATED ENGLISH) 2015 PROGRAM IN STATE UNIVERSITY OF SURABAYA (UNESA) Ismi Fauziyah English Education, Faculty of Language and Art, State University of Surabaya ismifauziyah@mhs.unesa.ac.id Abstrak Menulis adalah salah satu keterampilan yang perlu dikuasai oleh siswa-terutama untuk calon guru bahasa Inggris. Untuk itu, mahasiswa dari jurusan bahasa Inggris diharuskan mengambil kelas atau program IE (Integrated English) –mata kuliah satu semester untuk memberikan mahasiswa semua dasar keterampilan dan komponen bahasa. Sebagai pengembangan dari program IC (Intensive Course), IE program harus diteliti untuk mengetahui keefektifan dari program itu sendiri. Jadi, penelitian ini bertujuan untuk mengetahui efektivitas dari program IE dengan menganalisis perbedaan kualitas tulisan siswa di pre-test dan post-test program IE di lima elemen: isi, struktur, penggunaan bahasa, kosakata dan tata bahasa. Penelitian ini adalah penelitian ex-post facto karena hasil dari perbedaan kualitas tulisan siswa muncul secara natural setelah siswa mengikuti program IE 2015. Subjek penelitian ini adalah 30 mahasiswa program IE; masing-masing 10 siswa dalam kategori Intermediate, Pre-intermediate, dan Elementary. Setelah menganalisa tulisan pre-test dan post-test dari subjek penelitian, penelitian ini menemukan bahwa sebagian besar siswa mendapat kualitas yang sama di semua aspek dengan rata-rata 62,6%. Selain itu, sebagian besar siswa mendapat kualitas lebih baik dalam aspek penggunaan bahasa dan kosa kata; 40% siswa mendapat kualitas lebih baik. Secara keseluruhan, berdasarkan kesimpulan yang ada, Program IE memberikan sedikit efek untuk kemampuan menulis siswa dalam semua aspek. Kata Kunci: Menulis, Pre-test siswa, Post-test siswa, Program IE Abstract Writing is one of the skills that is needed to be mastered by EFL students-especially for English pre-service teachers. For that reason, UNESA freshmen students from English major have to take IE (Integrated English) program−one semester course to give the students all basic language skills and language components. As the development of IC (Intensive Course) program, IE program should be researched so that we can know the effectiveness of the program itself. Thus, this study was aimed to know the effectiveness of IE program by analyzing the writing quality difference in pre-test and post-test of IE program in five elements: content organization, language use, vocabulary and mechanic. This study was an ex-post facto research since the result of the students’ writing quality difference came naturally after the students joined IE 2015 program. The subject of this study was 30 students of IE program; each 10 students are in the category of Intermediate, Pre-intermediate, and Elementary. Having analyzed the pre-test and post-test writing of the subject, the research revealed that mostly the students got similar quality in all aspects by the mean of 62,6%. Moreover, the students develop mostly in language use and vocabulary aspect; 40% students got better quality. Overall, based on the conclusion drawn, IE program gives little effect to the students’ writing ability in all aspects. Keywords: Writing, Students’ pre-test, Students’ post-test, IE program